Olfactory Dysfunction and Its Relationship With Clinical Features of Parkinson's Disease - Zhou, Yangjie; He, Runcheng; Zhao, Yuwen; He, Yan; Hu, Yacen; Sun, Qiying; Xu, Qian; Tan, Jieqiong; Yan, Xinxiang; Tang, Beisha; Guo, Jifeng (Frontiers in Neurology, 2020)
Objective: To conduct an investigation into the reliability of assessing the olfactory function of patients with Parkinson's disease (PD) in a clinical setting of crowding patients in populated countries, such as China, by the hyposmia rating scale (HRS) and compare other non-motor features between patients with PD with olfactory dysfunction (PD-OD) and patients with PD without olfactory dysfunction (PD-NOD), according to the result of olfactory function assessed by the Sniffin' Sticks test. Methods: A total of 320 patients with clinically confirmed or clinically possible PD were recruited. Olfactory function of all participants was assessed with the HRS and the Sniffin' Sticks test. Demographic data and clinical information were collected, and patients were evaluated using standardized assessment protocols. With reference to the Sniffin' Sticks test, the specificity, sensitivity, coincidence rate, and kappa value of the HRS was computed, and then its reliability was evaluated. We divided patients into PD-OD and PD-NOD groups based on the results of olfactory function assessed by the Sniffin' Sticks test. Clinical manifestations were compared between PD-OD and PD-NOD. Results: The percentage of patients with OD determined by the Sniffin' Sticks test was 65.6%, and the percentage of those with OD was 55.6% when using the HRS measured olfactory function. With reference to the Sniffin' Sticks test, the specificity, sensitivity, coincidence rate, and kappa value of the HRS were 82.73, 75.71, 78.13%, and 0.55, respectively. The area under the receiver operating characteristic curve for the HRS was 0.793. There were no differences in demographic characteristics between the PD-OD and PD-NOD groups. The patients with hyposmia had more severe non-motor symptoms. Conclusion: The HRS is of great value as a self-assessment scale for evaluating olfactory function, especially in PD patients over 55 years old. Moreover, PD patients with hyposmia have more severe non-motor features than PD patients without hyposmia, mainly in terms of mood and constipation.